The association between dietetic consultation and time to dialysis for patients attending a pre‐dialysis clinic: A retrospective cohort study. Issue 5 (13th August 2019) - Notaras, Stephanie; Galea, Leanne; Lee, Paul; Mak, May; Lambert, Kelly; Makris, Angela
Abstract: Aim: A multidisciplinary approach, including dietetics, is considered the optimal model of care for dialysis preparation. Dietetic consultation (DC) focuses on symptom management and dietary changes to delay time to dialysis. Evidence of the effectiveness of DC on time to dialysis is limited. This study aimed to investigate the impact of DC on time to dialysis for patients attending a pre‐dialysis clinic. Methods: A retrospective cohort study was designed to include all patients attending outpatient pre‐dialysis clinics at a large metropolitan renal service between January 2014 and March 2018. Time to dialysis (days) was compared between patients that received DC and those who did not. Cox proportional hazards analysis allowing for adjustment of differences and confounders was undertaken. Results: A cohort of 246 patients was identified. Median estimated glomerular filtration rate was 16mL/min per 1.73 m 2 (interquartile range = 13–20) at initial pre‐dialysis clinic visit and 63% commenced dialysis during the study period. Only 41% of patients received dietetic consultation. Significantly fewer patients needed to commence dialysis in the DC group compared to the no‐DC group (hazards ratio 0.63; 95% confidence interval (CI) 0.45–0.89; P = 0.008 Cox proportion hazard). The DC group commenced dialysis significantly later than the no‐DC group; 933 days (95% CI 832–1034) versus 710 days (95% CI 630–790) respectively, after the initial pre‐dialysis clinic visit; log–rank 0.005. Conclusion: DC provided to patients attending a pre‐dialysis clinic was associated with a delayed time to dialysis. Standardised referral pathways to improve patient access to renal dietetic services are recommended to optimise care. SUMMARY AT A GLANCE: In this study, the impact of dietetic consultation on time to dialysis for patients attending a pre‐dialysis clinic was investigated. The authors found that dietetic consultation provided to patients was associated with a delayed time to dialysis. They concluded that standardized referral pathways to improve patient access to renal dietetic services were recommended to optimize care.